Effects of Pulsed-Wave Chromotherapy and Guided Relaxation on the Theta-Alpha Oscillation During Arrest Reaction - Cheron, Guy; Ristori, Dominique; Petieau, Mathieu; Simar, Cédric; Zarka, David; Cebolla, Ana-Maria (Frontiers in Psychology, 2022)
The search for the best wellness practice has promoted the development of devices integrating different technologies and guided meditation. However, the final effects on the electrical activity of the brain remain relatively sparse. We here performed the analysis of the alpha and theta electroencephalographic oscillations during the arrest reaction realized during a chromotherapy session performed in a dedicated room (Rebalance (RB) device), with an ergonomic bed integrating pulsed-wave light (PWL) stimulation and guided breathing exercise. We demonstrated that the PWL induced an evoked-related potential characterized by the N2-P3 components maximally recorded on the fronto-central locus and accompanied by an event-related synchronization of the delta-theta-alpha oscillation presenting a phase-locking of 20 to 40 % of the trials in the same frequency band. The power of the alpha and theta oscillations were analyzed before, during, and after the RB session. For this repeated arrest reactions testing were realized along with the whole RB session. We showed that the power of the alpha and theta oscillations measured during the arrest reactions for both eyes-open and eyes-closed states were significantly increased during the session in comparison to their values recorded before the RB session. In contrast, these increased powers were not observed in two different control groups of participants who stayed passively outside or inside of the RB room but without any type of stimulation